Convergence of the Collatz Sequence (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
For any natural number was created the supplement sequence, that is convergent together with the original Collatz sequence. The numerical parameter - index was defined, that is the same for both sequences. This new method provides the following results:• All natural numbers were distributed into six different classes;• The properties of index were found for the different classes;• For any natural number was constructed the bounded sequence of increasing numbers,    that is convergent together with the regular Collatz sequence.